Implementasi Good Corporate Governance Dalam Menanggapi Tindak Korupsi Study Kasus PT Pertamina - Admojo, Muhammad Yansen Suryo; Ramadhandy, Hary Kurnia; Afifuddin, Muhammad; Kusumaningtias, Rohmawati; Kusumaningsih, Ambar (Innovative: Journal Of Social Science Research, 2025)
The mega corruption case at PT Pertamina in 2023 with state losses of IDR 193.7 trillion reflects the failure of Good Corporate Governance (GCG) implementation in SOEs. This research analyzes the relationship between weak GCG and corruption and formulates strategies to strengthen governance. Using a qualitative case study approach through analysis of legal documents and literature, it is found that weak accountability, transparency and independence trigger systemic corruption. The failure of the three lines of defense exacerbates this condition. The research emphasized the importance of organizational culture reform and external oversight. Recommendations include strengthening the whistleblowing system, utilizing technology for transparency, and evaluating the ISO 37001 standard. The findings are relevant for GCG improvement in SOEs as well as enriching theoretical studies on post-scandal governance.